Penerapan Model Project Based Learning Sebagai Upaya Meningkatkan Motivasi dan Prestasi Belajar Kimia Siswa Kelas XII - Utami, Wiji Dwi; Astuti, Andari Puji; Wardani, Yuyun Eka (Journal of Lesson Study in Teacher Education, 2024)
This research is classroom action research carried out in two cycles. Each cycle consists of action planning stages, action implementation, observation/data collection and reflection. The research subjects were students in class XII-5 of SMA Negeri 4 Semarang for the 2024/2025 academic year. This research aims to increase student motivation and learning achievement in chemistry subjects on the concept of Electrochemical Cells. To achieve this goal, researchers applied the Project Based Learning learning model by creating a simple experimental or practicum project. The instruments used in this classroom action research are learning motivation questionnaires, video documentation and cognitive tests. The research results show that the average percentage of student learning motivation in the pre-cycle was 64.8%, then in cycle 1 it increased to 91% and cycle 2 to 95.6%. Meanwhile, the data on student learning achievement after taking action by applying the Project Based Learning model in cycle 1, the average was 83, then in cycle 2 it became 76. The chemistry learning achievement of these students experienced a decline due to several reasons, namely in cycle 2 the material discussed are Electrolysis Cells and Faraday's Law, where the content is more complex and students do not fully understand the prerequisite material.